Competence for Students' Future: Curriculum Change and Policy Redesign in China. (June 2019) - Wang, Tao
Purpose: This article aims to provide a policy review of the new national curriculum program and standards for high school education announced in January 2018 and analyze the key features of curriculum change in China. Design/Approach/Methods: Applying textual analysis, this article interprets the significant changes in the national curriculum program and standards and further discusses these changes based on literature and research on curriculum. Findings: Corresponding to the international trends on core competencies, China takes a further step and designs subject core competencies to narrow the gap between theories, policy, and practice. The new national curriculum highlights the coherent design in curriculum, textbooks, teaching, and assessment. Yet there are still puzzles and challenges in high stakes examination, diverse contexts, and curriculum implementation. Originality/Value: This article might facilitate the understanding of the current high school curriculum in China, especially on its features, changes, contexts, and history.